2008
DOI: 10.1038/nrg2348
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of gene expression between organellar and nuclear genomes

Abstract: Following the acquisition of chloroplasts and mitochondria by eukaryotic cells during endosymbiotic evolution, most of the genes in these organelles were either lost or transferred to the nucleus. Encoding organelle-destined proteins in the nucleus allows for host control of the organelle. In return, organelles send signals to the nucleus to coordinate nuclear and organellar activities. In photosynthetic eukaryotes, additional interactions exist between mitochondria and chloroplasts. Here we review recent adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
542
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(554 citation statements)
references
References 140 publications
(179 reference statements)
8
542
0
4
Order By: Relevance
“…Several studies indicate a close relationship between the rDNA arrays, ribosomal biogenesis and the mitochondria [10][11][12][13] . For instance, recent evidence points to the import of 5S rRNAs into the mitochondria through a highly regulated process 35,36 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies indicate a close relationship between the rDNA arrays, ribosomal biogenesis and the mitochondria [10][11][12][13] . For instance, recent evidence points to the import of 5S rRNAs into the mitochondria through a highly regulated process 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…These results might reflect the synchronization of GE between the nuclear and mitochondrial genomes in a concerted effort to control proper levels of protein production for mitochondria assembly and intracellular homeostasis. Retrograde signalling is an essential mechanism in which organelles communicate with the nucleus to convey a response from fluctuating environmental or cellular conditions 10 . Indeed, we found that genes whose expression is negatively correlated with rDNA dosage were functionally enriched for carbonyl reductase (NADPH) activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because mt genes are tightly coadapted with N‐mt genes (Woodson and Chory 2008; Lane 2011; Burton et al. 2013), adaptive divergence in a mt gene will inevitably entail coevolution with its coadapted N‐mt genes (Hill 2014; Levin et al.…”
Section: Speciation Via Mitonuclear Coevolution To Maintain Coadaptationmentioning
confidence: 99%
“…Coordinated expression of organelle genome-encoded and nuclear genome-encoded genes is fundamental to a range of cellular processes in eukaryotes 1,2 . Although mitochondrial functions are conserved among eukaryotes, genome structure and the regulatory mechanisms for gene expression in mitochondria are, surprisingly, quite divergent 3 .…”
mentioning
confidence: 99%